MENINGKATKAN KEMAMPUAN BERBICARA SISWA DALAM MENCERITAKAN KEGEMARAN MELALUI TEKNIK PERCAKAPAN - Ngalimun, Ngalimun (Journal of Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2016)
Their speaking ability by using conversational techniques arevery important and far-reaching. This is shown by the results of the acquisition of scores of observations made respondents, who answered "always" in 15 questions with a score of 869.68 tally with an average of 57.98 %, a score answered "sometimes" in the amount of 630, 32 with an average of 42.02 %, while the answer is not in the amount of 0 with an average of 0 % or no answer . If the comparison between the scores three alternative answers of "yes" has the greatest score, so it can be concluded that the conversation technique can improve their speaking ability in communicating his love to the category quite well. Increasing students' speaking ability in telling the student craze is influenced by several factors, among others, is the way of pronunciation tones and how to communicate.